2004
DOI: 10.1021/jm021009+
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Labeled Benzodiazepines:  Development of Small Ligands for Receptor Binding Studies Using Fluorescence Correlation Spectroscopy

Abstract: To investigate benzodiazepine receptor binding studies by fluorescence correlation spectroscopy (FCS), the four fluorophores fluorescein, tetramethylrhodamine, Oregon Green 488, and Alexa 532 were coupled to the benzodiazepine Ro 07-1986/602 (Ro). Binding assays to polyclonal antibodies to benzodiazepines and at the native benzodiazepine receptor on the membrane of rat hippocampal neurons were established to examine the dye-labeled ligands for their benzodiazepine character and their binding behavior. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Ligand-binding affinities, receptor densities and off rates for a number of different ligand–receptor combinations have all been determined successfully. In each case, even in heterogeneous cell populations from primary sources, useful quantitative information about ligand–receptor interactions was obtained, supporting the applicability of such methodology to studying pharmacology in biopsy samples [18,19,22–25] . In the case of the insulin C-peptide [18,22,23] , kavain [25] and glucocorticoid receptors [26,27] , the FCS data provided the first direct evidence for the existence of specific cell-surface GPCRs for these ligands.…”
Section: Fcs and Its Application To Studying Ligand–receptor Bindingmentioning
confidence: 67%
“…Ligand-binding affinities, receptor densities and off rates for a number of different ligand–receptor combinations have all been determined successfully. In each case, even in heterogeneous cell populations from primary sources, useful quantitative information about ligand–receptor interactions was obtained, supporting the applicability of such methodology to studying pharmacology in biopsy samples [18,19,22–25] . In the case of the insulin C-peptide [18,22,23] , kavain [25] and glucocorticoid receptors [26,27] , the FCS data provided the first direct evidence for the existence of specific cell-surface GPCRs for these ligands.…”
Section: Fcs and Its Application To Studying Ligand–receptor Bindingmentioning
confidence: 67%
“…[ 6,7 ] Our aTF‐based FRET sensors utilize the analyte‐responsive unbinding of the donor‐labeled aTF and its acceptor‐labeled cognate DNA sequence to effect a large change in the donor–acceptor distance. Thus, these FRET sensors eliminate the need to dye‐label ligands, which can change their binding behavior, [ 12 ] while enabling the substantial signal changes produced through complete dissociation of the donor and acceptor fluorophores ( Figure ).…”
Section: Figurementioning
confidence: 99%
“…Recently, the influence of the dye moiety on the receptor binding and signaling of fluorescently labeled ligands has been demonstrated in several publications [31,32].…”
Section: Gpcr Ligandsmentioning
confidence: 99%
“…Hegener et al showed for example that coupling Alexa532 to the Therefore, predictions about the binding affinities and the pharmacological properties of fluorescently labeled ligands are not possible and have to be validated. Examples for such series of experiments investigating the influence of different fluorophores and/or linkers on the pharmacology of receptor ligands were published by Baker et al[30] and Hegener et al[31].…”
mentioning
confidence: 99%